Analysis of Antibiotic Consumption by AWaRe Classification in Shandong Province, China, 2012–2019: A Panel Data Analysis - Jia Yin (Frontiers Media S.A., 2021)
Introduction: This study aims to examine the changes in trends and patterns of clinical consumption of antibiotics in Shandong, China based on Access, Watch, and Reserve (AWaRe) Classification after 10-years national antibiotic stewardship.Methods: Antibiotic consumption data of all health care institutions for the period of 2012–2019 were obtained from the Drug Centralized Bidding Procurement System of Shandong. Shandong is a province that has the second-largest population in China. Five of the 16 cities in Shandong were high-income areas (HIAs) and the other 11 cities were grouped into upper-middle-income areas (UMIAs). The main outcome measures were the antibiotic consumption rates (DDD per 1,000 inhabitants per day, DID) and the proportions of different groups of antibiotics.Results: The overall antibiotic consumption rate increased from 12.859–15.802 DID between 2012 and 2014, then continuously decreased to 9.771 DID in 2019. The consumption rate of access, watch, and reserve antibiotics have reduced since 2014 with a compound annual growth rate of −10.1, −9.0, and −8.1%, respectively. During 2012–2019, the access group proportion reduced from 50.0 to 44.9%, while the proportion of the watch group increased from 42 to 45.2%. The antibiotic consumption rate increased from 2012 to 2019 (from 7.38 to 9.12 DID) in the HIAs but sharply decreased in the UMIAs from 2014 to 2019 (from 17.94 to 10.05 DID). The watch antibiotics had the highest proportion of consumption in the HIAs (55.3% in 2019), while the access group had the highest proportion of consumption in the UMIA (49.5% in 2019).Conclusion: The antibiotic stewardship policies launched in the last 10 years have contributed to reducing the clinical antibiotic consumption in Shandong. These policies have different effects on areas with different economic levels. The pattern of antibiotic consumption is still inappropriate in China as the watch group of antibiotics was consumed the most.